Different neural routes to autobiographical memory recall in healthy people and individuals with left medial temporal lobe epilepsy. (February 2018) - McCormick, Cornelia; Moscovitch, Morris; Valiante, Taufik A.; Cohn, Melanie; McAndrews, Mary Pat
Abstract: Individuals with medial temporal lobe epilepsy (mTLE) are poor at recalling vivid details from autobiographical memories (AM), instead retrieving gist-like schematic memories. Recent research has suggested that this impoverished recall in comparison to controls may reflect (1) differential engagement of anterior vs posterior regions of the hippocampus (HC) and/or (2) differences between the engagement of the HC vs the ventromedial prefrontal cortex (vmPFC). Here we examined these hypotheses by comparing connectivity amongst hippocampal regions and between vmPFC and other brain regions during construction (retrieval of a particular event) vs elaboration (retrieval of perceptual detail) phases of AM recall in 12 individuals with left mTLE and 12 matched controls. Whereas functional connectivity amongst hippocampal regions changed from AM construction to elaboration in controls, the pattern of intra-hippocampal connectivity was unvarying in patients. Furthermore, patterns of connectivity from the vmPFC differed between phases in distinct ways in the two groups of participants. In patients, vmPFC activation was correlated with other prefrontal and lateral temporal cortices during construction and with visual-perceptual cortices during elaboration. While controls did not show a difference in whole-brain connectivity, they did uniquely show a dynamic shift from vmPFC connectivity to anterior HC during construction and to posterior HC during elaboration. Together, these findings suggest that impoverished AM recall in mTLE is a consequence of reduced activation and flexibility of bilateral hippocampal networks and greater reliance on neocortical contributions to memory retrieval. Highlights: Dynamic bilateral HC interactions between AM retrieval stages are reduced in mTLE. vmPFC connections to anterior and posterior HC differentiate AM retrieval stages in controls. vmPFC-neocortical connectivity coordinates AM construction and elaboration in mTLE. Impoverished AM recall in mTLE reflects reduced hippocampal and greater neocortical contributions.